Effect of Frailty on Functional Gain, Resource Utilisation, and Discharge Destination: An Observational Prospective Study in a GEM Ward. (17th February 2014) - Kawryshanker, Sujatha; Raymond, Warren; Ingram, Katharine; Inderjeeth, Charles A.
Abstract : Background . A geriatric evaluation and management unit (GEM) manages elderly inpatients with functional impairments. There is a paucity of literature on frailty and whether this impacts on rehabilitation outcomes. Objectives . To examine frailty score (FS) as a predictor of functional gain, resource utilisation, and destinations for GEM patients. Methods . A single centre prospective case study design. Participants (n = 136 ) were ≥65 years old and admitted to a tertiary hospital GEM. Five patients were excluded by the preset exclusion criteria, that is, medically unstable, severe dementia or communication difficulties after stroke. Core data included demographics, frailty score (FS), and functional independence. Results . The mean functional improvement (FIM) from admission to discharge was 11.26 (95% CI 8.87, 13.66; P < 0.001 ). Discharge FIM was positively correlated with admission FIM (β = 0.748 ; P < 0.001 ) and negatively correlated with frailty score (β = − 1.151 ; P = 0.014 ). The majority of the patients were in the "frail" group. "Frail" and "severely frail" subgroups improved more on mean FIM scores at discharge, relative to that experienced by the "pre-frail" group. Conclusion . All patients experienced functional improvement. Frailer patients improved more on their FIM and improved relatively more than their prefrail counterparts. Higher frailty correlated with reduced independence and greater resource utilisation. This study demonstrates that FS could be a prognostic indicator of physical independence and resource utilisation.